Risk factors for caesarean section in primigravidae - Preeti Malapure; Sumayya; Rajeshwari P; Sreelatha S (Barpeta Obstetrics and Gynaecological Society, 2019)
Objectives: To determine the antepartum and intrapartum risk factors leading to caesarean section in Primigravidae. Methods: A prospective study of 100 patients conducted in the department of Obstetrics and Gynaecology from January 2018 to June 2018. Data collected included the age of the patient, obstetric history, gestational age, clinical symptoms, antepartum and intrapartum risk factors for LSCS. Results: The most common antepartum risk factor for caesarean section in primigravidae was found to be fetal distress (41%) and the most common intrapartum finding was meconium stained liquor (27%). Conclusion: Presence of risks complicating pregnancies has increased the rates of primary caesarean section. It is prudent to carefully weigh the risks and benefits associated with caesarean section in order to improve the pregnancy outcome.